The assignment [videorecording (DVD)] - Hill, Walter, 1942-; Rodriguez, Michelle; Shalhoub, Tony, 1953-; LaPaglia, Anthony; Weaver, Sigourney, 1949- (Lionsgate, 2017)
Ace assassin Frank Kitchen is double crossed by gangsters and falls into the hands of a vengeful surgeon known as The Doctor, whose brother was recently murdered by Frank.